2009
DOI: 10.1016/j.ejvs.2009.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine and Peripheral Arterial Disease: Systematic Review and Meta-analysis

Abstract: Patients with PAD have significantly higher Hcy levels than unaffected controls. However, we did not find any robust evidence on clinically beneficial effects of folate supplementation in PAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
1
7

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(76 citation statements)
references
References 45 publications
3
63
1
7
Order By: Relevance
“…The vitamin amount in standard food fails to lower homocysteine levels. Recent literature information is consistent with our data concerning the lack of benefit from folate supplementation [24] Statistical analysis (AnOVA-one-way) indicated significant differences within groups (*p < 0.0001, when compared to the initial measurement), but no significant differences between groups.…”
Section: Resultssupporting
confidence: 79%
“…The vitamin amount in standard food fails to lower homocysteine levels. Recent literature information is consistent with our data concerning the lack of benefit from folate supplementation [24] Statistical analysis (AnOVA-one-way) indicated significant differences within groups (*p < 0.0001, when compared to the initial measurement), but no significant differences between groups.…”
Section: Resultssupporting
confidence: 79%
“…Os autores dessas revisões enfatizaram que a homocisteína é fácil de ser avaliada e, mais importante, fácil e barata de ser tratada, muito embora alguns estudos clínicos interroguem os efeitos benéficos dessa terapêutica 90 . Por outro lado, o declínio da mortalidade cardiovascular nos Estados Unidos…”
Section: Efeitos Do Tratamento Da Hiper-homocisteinemia Sobre a Morbiunclassified
“…The prevalence of aspirin, clopido- high-sensitivity C-reactive protein, Total-C: total cholesterol, LDL-C: low-density lipoprotein cholesterol, HDL-C: high-density lipoprotein cholesterol, RLP-C: remnant-like particle cholesterol, TAT: thrombin-antithrombin complex, PIC: plasmin-2 plasmin inhibitor complex, BNP: brain natriuretic peptide, ACE: angiotensin-converting enzyme, ARB: angiotensin receptor blocker tion, the fibrinogen level is particularly associated with the severity and potential for the further development of PAD 26) and functions as an independent risk factor for CAD 25) . Hyperhomocysteinemia is an independent risk factor for atherosclerosis and a stronger risk factor for PAD than for CAD 16,17) , with an association with death or severe vascular events in patients with PAD 27) . We previously found that a high plasma homocysteine level is also a risk factor for CLI as well as PAD 17) .…”
Section: Discussionmentioning
confidence: 99%
“…Homocysteine is an intermediate metabolite of methionine that contributes to cardiovascular disease via mechanisms such as endothelial dysfunction, increased lipid permeability and vascular inflammation 14,15) . Hyperhomocysteinemia is an independent risk factor for PAD and CAD 16,17) . Hence, the combination of high homocysteine and Lp(a) levels synergistically increases the likelihood of developing CAD 15) .…”
Section: Introductionmentioning
confidence: 99%